2020
DOI: 10.1109/access.2020.2974407
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Vector Hysteresis Model Utilizing Enhanced Neural Network Based on Collaborative Algorithm

Abstract: A hysteresis model, based on the enhanced neural network with parallel strategy, is put forward for the prediction of the accurate magnetic behavior of electrical steel sheets (ESSs). Aimed at overcoming the drawbacks such as low convergence rate and convenient to trap into local optimum in the conventional back-propagation neural network (BPNN), a novel collaborative BPNN learning algorithm is introduced according to the error back propagation mechanism and particle swarm optimization (PSO). The reasonable se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In many cases the non‐linearity of the magnetic core, together with the presence of non‐sinusoidal and strongly distorted current and voltage waveforms becomes a critical issue of the design. Moreover, the real magnetic field in these applications is a vector quantity, and the magnetic hysteresis modeling should be conveniently adapted to that 8–17 . In literature, many studies dealing with this issue have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases the non‐linearity of the magnetic core, together with the presence of non‐sinusoidal and strongly distorted current and voltage waveforms becomes a critical issue of the design. Moreover, the real magnetic field in these applications is a vector quantity, and the magnetic hysteresis modeling should be conveniently adapted to that 8–17 . In literature, many studies dealing with this issue have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the real magnetic field in these applications is a vector quantity, and the magnetic hysteresis modeling should be conveniently adapted to that. [8][9][10][11][12][13][14][15][16][17] In literature, many studies dealing with this issue have been reported. Analytical formulas based on the losses separation criterion have been proposed: the magnetic power losses are separated into static hysteresis losses and dynamic losses.…”
Section: Introductionmentioning
confidence: 99%
“…The principal scope of this research is to give a contribution to the development of the dynamic models of hysteresis for innovative soft ferromagnetic materials, exploiting artificial neural networks (ANNs). Until now, ANNs have been successfully applied in the development of both scalar [23][24][25] and vector models of static hysteresis [26][27][28], but fewer studies also take the rate dependence into account [29][30][31][32]. The main advantages of neural network-based models are related to their cheap memory allocation and high computational speed, especially when implemented at a low level of abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large amount of papers dealing with the reproduction of the scalar hysteresis phenomenon via NN-based models, the same approaches for vector hysteresis problems have been less explored [25]. The application of a neural system consisting of an assembly of feedforward networks was proposed in [26] to reproduce vector magnetization patterns for Fe-Si laminated steels, but the comparison with the experimental data only covered the rotational loops under circular magnetic induction with sinusoidal waveforms. In addition, the problem of power loss prediction has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The second scope of the work is therefore to deal with hysteresis modeling and power loss estimation, taking into account generic supply conditions. The vector NN model, similar to the one introduced in [26] and also discussed in [28], was implemented in a Matlab ® computing environment and is presented in Section 3. It is seen that the model can be opportunely identified only by exploiting the rotational loops with circular magnetic induction trajectories, whereas the other measured processes can be used as test cases for validation.…”
Section: Introductionmentioning
confidence: 99%